P-679 Comparison of hormone replacement treatment (HRT) and true-natural cycle (t-NC) protocols for endometrial priming: An analysis of 1, 815 warmed blastocyst transfer cycles. (30th June 2022) - Erturk, A; Mumusoglu, S; Polat, M; Erden, M; Ozbek, I. Y; Ozten, G; Esteves, S; Humaidan, P; Yarali, H
Abstract: Study question: Does the ongoing pregnancy rate (OPR) of HRT with or without GnRH-agonist suppression and t-NC protocols differ in patients undergoing warmed blastocyst transfer? Summary answer: HRT, with or without GnRH-agonist suppression, and t-NC protocols are associated with comparable OPRs in patients undergoing warmed blastocyst transfer. What is known already: Despite the worldwide increase in frozen embryo transfer cycles, the most optimal protocol for priming of the endometrium is debated. Although HRT offers flexibility, recent evidence points tot-NC being superior to HRT regarding safety, i.e., maternal, obstetric, and neonatal outcomes.However, there are still conflicting data regarding pre-clinical losses and reproductive outcomes when comparing the two protocols. Study design, size, duration: In this longitudinal prospective study, 1, 815 consecutive patients undergoing 1, 815 warmed blastocyst transfer cycles at the Anatolia IVF Centre, Ankara, between 2015-2021, were included. HRT with pituitary suppression was the protocol of choice during 2015- 2017, whereas HRT without suppression and t-NC were more commonly employed during the latter part of the period. Participants/materials, setting, methods: All patients with an available day-5/6 vitrified blastocyst(s) were included. Each patient was included only once. The three protocols were t-NC and HRT - with or without suppression. The prerequisites for t-NC was being a local patient with regular menstrual cycles. For t-NC, neither human chorionic gonadotropin (hCG) nor luteal phase support was administered. The primary outcome measure was OPR, defined as pregnancy >12 weeks of gestation. Main results and the role of chance: Of the 1, 815 cycles, 124 were t-NC, 477 were HRT with suppression, and 1, 214 were HRT without suppression. For the stimulated cycles leading to FET, no difference was seen among the three groups regarding female age, body mass index, duration of infertility, number of previous embryo transfer attempts, ovarian stimulation protocol, estradiol levels on the day of hCG trigger, number of oocytes retrieved, number of preimplantation genetic testing-aneuploidy, freeze-all cycles and number of embryos transferred. The positive pregnancy test rates of the HRT protocol with or without suppression were higher when compared with that of t-NC (63.7%, 66.6%, and 58.1%, respectively; p = 0.05). The respective figure for clinical pregnancy rates were 56.6%, 60.8% and 55.6% (p = 0.07). However, the pre-clinical (biochemical) loss rates (11.9%, 10.9%, and 4.9%, respectively; p = 0.05), as well as the miscarriage rates (11.9%, 10.9%, and 4.9%, respectively; p = 0.04), were higher in the HRT groups with or without suppression compared to those of t-NC. The OPRs of t-NC, HRT with or without suppression were comparable (53.2%, 45.1%, and 49.0%, respectively; p = 0.73). The protocol for endometrial priming was not an independent predictor of ongoing pregnancy at logistic regression analysis when potential confounders were used as covariates (OR = 0.998; 95%CI 0.669-1.490, p = 0.99). Limitations, reasons for caution: The longitudinal study design and the lack of obstetric and perinatal outcome data are limitations. Wider implications of the findings: Compared with t-NC, the HRT protocol with/without suppression is associated with higher positive pregnancy test rates albeit increased pre-clinical and clinical loss rates, resulting incomparable OPRs. When compared with t-NC, the HRT protocol could be associated with enhanced endometrial receptivity at the expense of decreased selectivity. Trial registration number: not applicable